2021
DOI: 10.1111/jocn.15980
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nurses’ intention to accept COVID‐19 vaccination: A cross‐sectional study in five European countries

Abstract: Aims and Objectives:To investigate nurses' intention in accepting COVID-19 vaccination and the factors affecting their decision.Background: COVID-19 vaccination has started in most European countries with healthcare personnel being the first group receiving the vaccine shots. Their attitude towards vaccination is of paramount significant as their role in the frontline could help in the awareness of general population. Methods:A study was conducted in Albania, Cyprus, Greece, Spain and Kosovo with the use of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 41 publications
(62 reference statements)
6
49
0
1
Order By: Relevance
“…This alternative or concurrent explanation appeared to be supported by the positive bias shown for the relational COVID-negative, indicating that people tended to associate the disease with negative targets more easily than with positive ones. In light of this result, the study supports previous results obtained with self-report measures in which individuals showed higher compliance to vaccination as their risk perception towards the disease increased [ 23 , 45 ], or if they felt the vaccine was safe or not harmful [ 27 ]. Thus, our study showed that the population tends to get vaccinated because they trust the vaccination and fear the disease or the infection [ 2 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This alternative or concurrent explanation appeared to be supported by the positive bias shown for the relational COVID-negative, indicating that people tended to associate the disease with negative targets more easily than with positive ones. In light of this result, the study supports previous results obtained with self-report measures in which individuals showed higher compliance to vaccination as their risk perception towards the disease increased [ 23 , 45 ], or if they felt the vaccine was safe or not harmful [ 27 ]. Thus, our study showed that the population tends to get vaccinated because they trust the vaccination and fear the disease or the infection [ 2 ].…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the development of COVID-19 vaccines was very rapid, so people felt that there was a higher risk of this vaccination in comparison to previous ones, but at the same time knew less about its benefits and costs [ 19 ]. The literature on COVID-19 underlined a direct relationship between the perception of the risk of being infected and the propensity to get vaccinated [ 20 , 21 , 22 , 23 ]. This factor can cause the level of hesitancy to rise six-fold in people who are confident that they will not be infected [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, we observed significant gender disparities that females were less likely to get a COVID-19 vaccine relative to males, ( Daly and Robinson, 2021 , Latkin et al, 2021 , Khubchandani et al, 2021 , Reiter et al, 2020 ) which is consistent with the findings reported in Canada, European and Asian countries. ( Ogilvie et al, 2021 , Patelarou et al, 2021 , Murphy et al, 2021 , Wang et al, 2020 ) This result is not surprising as females are more cautious when making health decisions. ( Ek, 2015 ) Our review provided additional clues that females did not believe the vaccine would be safe or effective.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, WHO highlights that health care sector personnel can play an important role in the successful implementation of a vaccination policy, as they can contribute to vaccination promotion and act as role models for the community [ 3 ]. Recent studies revealed that doctors’ advice for COVID-19 vaccination counts in favor of vaccine acceptance [ 10 , 11 , 12 ]. In Greece, the current COVID-19 vaccination project involves all personnel working in Primary Health Care Centers (PHCC) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%